If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -2x + 3y = 2y Combine like terms: 3x + -2x = 1x 1x + 3y = 2y Solving 1x + 3y = 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 1x + 3y + -3y = 2y + -3y Combine like terms: 3y + -3y = 0 1x + 0 = 2y + -3y 1x = 2y + -3y Combine like terms: 2y + -3y = -1y 1x = -1y Divide each side by '1'. x = -1y Simplifying x = -1y
| 0.3x-0.1=0.2x+4 | | 6-4h=6h-8h | | x=-3(-1)+7 | | (4x-5)=(4x-4) | | 0=5t^2-15t+10 | | 6x-19=180 | | 22+5x=6x | | -6y+14-4y=24 | | 0.3x-0.1=0.2+4 | | 4x-5=x-4 | | 7(5p+9)= | | 5-5w+x=0 | | 3+5+x=19 | | 7x+13-6x=-8+12 | | 5+6h=6+2h | | 3(5+7x)=-132 | | 5+6h=6 | | 2y=4(0)+5 | | 4x+5(6x-18)=148 | | 2y=2(0)+1 | | 7x+2(x+15)=84 | | 23x+15=8x | | 8x+7-3x=-6x-15+x | | 2x+7(3x-4)=179 | | 3y+2x=62 | | x^2+5-(7+3*x)= | | 2.3*(-1.2)= | | 7-7x=34-14x | | -35+8+m=-8+11 | | 6x+2(4x+15)=198 | | -1.1*(-8)= | | -15*(-3)= |